A DNA vaccine encoding foot-and-mouth disease virus B and T-cell epitopes targeted to class II swine leukocyte antigens protects pigs against viral challenge - Borrego, Belén (2011)
Development of efficient and safer vaccines against foot-and-mouth disease virus (FMDV) is a must. Previous results obtained in our laboratory have demonstrated that DNA vaccines encoding B and T cell epitopes from type C FMDV, efficiently controlled virus replication in mice, while they did not protect against FMDV challenge in pigs, one of the FMDV natural hosts. The main finding of this work is the ability to improve the protection afforded in swine using a new DNA-vaccine prototype (pCMV-APCH1BTT), encoding FMDV B and T-cell epitopes fused to the single-chain variable fragment of the 1F12 mouse monoclonal antibody that recognizes Class-II Swine Leukocyte antigens. Half of the DNA-immunized pigs were fully protected upon viral challenge, while the remaining animals were partially protected, showing a delayed, shorter and milder disease than control pigs. Full protection in a given vaccinated-pig correlated with the induction of specific IFNγ-secreting T-cells, detectable prior to FMDV-challenge, together with a rapid development of neutralizing antibodies after viral challenge, pointing towards the relevance that both arms of the immune response can play in protection. Our results open new avenues for developing future FMDV subunit vaccines.